Features of the skin microbiome in patients with chronic eczema during relapse - Dashchuk, Andrii; Mishyna, Maryna; Dashchuk, Andrii; Dobrzhanska, Yevheniia; Marchese, Alessandra; Pisi, Roberta; Bondarenko, Olha; Aiello, Marina; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2026)
Background and Aim: In the presence of eczema, the skin serves as a reservoir for endogenous and exogenous infectious agents. Therefore, in order to understand the mechanism of interaction between microorganism and the macroorganism, it is necessary to study the characteristics of the skin microbiota in individuals with chronic eczema. The aim of this study is to determine the characteristics of changes in the skin microbiome during relapse of chronic eczema depending on age and gender. Methods: The results of a study of 80 patients with chronic eczema during relapse are presented. The study of the skin microbiome used a culture-based method. Isolated pure cultures of clinical strains were identified using MICRO-LA-TEST® identification kits. Microorganism suspensions with a specific concentration of microbial cells were prepared using a Densi-La-Meter. Results: Gram-positive microflora, represented by Staphylococcus spp. and Streptococcus spp., predominated in the affected areas. A significant increase in microbial colonisation density was observed in men aged 61 to 81 years. In the control group, on the contrary, the highest colonisation density was observed in individuals aged 41 to 60 years. Conclusions: Dysbiotic changes were detected in affected and unaffected skin areas during chronic eczema recurrences across all age groups. It was found that women suffer more often (67.5% of cases) than men. However, the density of microorganism colonisation of scin areas was higher in men, which may be due to hormonal differences and the influence of estrogens on the microbiome of the skin and mucous membranes.